METODE DAN CORAK TAFSIR AL-QUR'AN (TAHLILI, IJMALI, MUQARAN, MAUDU'I) - Achmad Gufron; Alex Achsan; Arya Duta Al Hajry; Muhammad Najib Alwi; Faishol Faishol (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This study examines the four main methods of Qur'anic exegesis: Tahlili, Ijmali, Muqaran, and Maudhu'i. The aim of this research is to explore the definitions, characteristics, advantages, limitations, and applications of each method in interpreting Qur'anic verses. The research employs a literature review methodology by analyzing various scholarly works and Qur'anic exegesis from classical to contemporary scholars. The findings indicate that each method has a distinct approach: Tahlili offers a detailed and in-depth interpretation of the Qur'anic text, while Ijmali provides a broader and more general understanding. Muqaran allows for a comparative analysis between different exegeses, while Maudhu'i focuses on thematic exegesis, offering a comprehensive view of specific topics in the Qur'an. The study concludes that understanding these four methods enriches and provides a more nuanced interpretation of the Qur'an, relevant to academic, religious, and social contexts. Keywords: Qur'anic exegesis, Tahlili, Ijmali, Muqaran, Maudhu'i